Determination and traceability of matrine and oxymatrine in Chinese acacia honey. Issue 7 (5th July 2022) - Zongyan, Cui; Hong, Lin; Lei, Chen; Xuezhe, Huang; Tao, Ding; Jinzhong, Xu
Abstract: Background: Matrine and oxymatrine were detected in Chinese acacia honey. In order to study their sources, some acacia honey samples from different years and producing areas were collected, and a method for the determination of matrine and oxymatrine in honey by liquid chromatography–tandem mass spectrometry was established. The linear range was 1–100 ng/ml and the limit of quantification was 1.0 μg/kg. At the spiking level of 1.0, 2.0, and 10.0 μg/kg, the recoveries were in the range of 71.3%–104.6% and RSD was 1.3%–4.8%. The method can be used for the determination of matrine and oxymatrine in honey and plant flowers, leaves, and stems. Results: Matrine and oxymatrine were detected in 27 of 39 acacia honey samples collected in 2021. In samples from the other years, 14 of the 18 samples of acacia honey tested were found positive. No matrine or oxymatrine residues were detected in the flowers of acacia, whilst high levels of matrine and oxymatrine were detected in the flowers, leaves and stems of the Sophora davidii Skeels. The highest level of oxymatrine and matrine detected were 283.9 and 58.8 mg/kg, respectively, more than a thousand times higher than the content detected in acacia honey (unit: μg/kg). Conclusions: It was confirmed that the matrine and oxymatrine were inevitable in acacia honey of northwest China and originated from the introduction of S. davidii Skeels nectar.